Free Energy Relationships in Electrochemistry: A History That Started in 1935 - Zagal-Moya, J; Zagal-Moya, J (2011)
This article is a historical overview of free energy relationships in electrochemistry with the purpose of giving the reader an integrated view on how these correlations are interconnected in various aspects starting with free energy correlations for outer-sphere and inner-sphere processes, Tafel correlations, the Butler-Volmer equation, and electron transfer theories. The citation of the literature is far from complete and is aimed to stimulate the reader to further reading. © 2011 Springer-Verlag.